2019
DOI: 10.3390/s19102277
|View full text |Cite
|
Sign up to set email alerts
|

UV Sensitivity of MOS Structures with Silicon Nanoclusters

Abstract: Selective UV sensitivity was observed in Metal-Oxide-Semiconductor structures with Si nanoclusters. Si nanocrystals and amorphous Si nanoparticles (a-Si NPs) were obtained by furnace annealing of SiOx films with x = 1.15 for 60 min in N2 at 1000 and 700 °C, respectively. XPS and TEM analysis prove phase separation and formation of Si nanocrystals in SiO2, while the a-Si NPs are formed in SiO1.7 matrix. Both types of structures show selective sensitivity to UV light; the effect is more pronounced in the structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Ultraviolet (UV) photodetectors (PDs) have drawn much attention because of their wide range of applications such as UV monitoring in the environment, flame sensing, missile launch detection, biological sensing, and space communications [1][2][3]. Although silicon photodiodes have been commonly used as excellent UV detection devices, they generally exhibit some inherent limitations: (i) they require appropriate filters to block the photons in the visible and infrared ranges, (ii) they need to be cooled down to avoid changes in the dark current, and (iii) they are susceptible to degradation under exposure to UV light with energies that are much higher than those of the semiconductor bandgap [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV) photodetectors (PDs) have drawn much attention because of their wide range of applications such as UV monitoring in the environment, flame sensing, missile launch detection, biological sensing, and space communications [1][2][3]. Although silicon photodiodes have been commonly used as excellent UV detection devices, they generally exhibit some inherent limitations: (i) they require appropriate filters to block the photons in the visible and infrared ranges, (ii) they need to be cooled down to avoid changes in the dark current, and (iii) they are susceptible to degradation under exposure to UV light with energies that are much higher than those of the semiconductor bandgap [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the applied electric field (negative voltage in the gold contact and positive voltage in the back contact), part of the photogenerated carriers diffuse under the contact. Likewise, these carriers are separated by an electric field and can tunnel through the Si-ncs, resulting in increased current flow through the MIS structure [ 16 , 37 , 38 , 39 , 40 ]. As mentioned above, the device responded well to light regardless of the opaque surface of the contacts, so another type of transparent contacts must be investigated, where the responsivity may be much greater than that shown in Figure 18 ; this is because gold contacts have high reflectivity in the visible infrared range (50% to 95% from 500 nm to 900 nm, respectively) [ 41 ], so at wavelengths greater than 500 nm, light may not penetrate into the contacts.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, metal-insulator-semiconductor structures with SRO as the insulator and active layer provide good results under illumination conditions [ 16 , 17 , 18 , 19 ]. In previous reports, it was found that the SRO-MIS structure exhibits an active optical response in the ultraviolet range due to the radiation emission of silicon nanocrystals (Si-ncs) formed in SRO films and the defects present in the mixed-phase nanostructure material [ 16 , 17 , 18 , 19 ]. Due to its high profitability and low cost of mass production, this material can be integrated with standard manufacturing processes in the microelectronics industry based on silicon technology.…”
Section: Introductionmentioning
confidence: 99%